NIMG-06. KINETICS-BASED RESPONSE METRIC DISCRIMINATE IMPROVED OUTCOMES FOR PATIENTS RECEIVING BEVACIZUMAB-BASED THERAPIES. (5th November 2018) - Singleton, Kyle; Kirby, Destiney; Johnston, Sandra; Rickertsen, Cassandra; De Leon, Gustavo; Whitmire, Scott; Clark-Swanson, Kamala; Morris, Yvette; Bendok, Bernard; Mrugala, Maciej; Porter, Alyx; Swanson, Kristin
Abstract: INTRODUCTION: Evaluating treatment response in glioblastoma is a difficult task for clinicians, particularly in recurrent disease. Current response metrics focus on changes in imageable tumor burden which can be ambiguously affected by anti-angiogenic therapy. In previous work, we reported the ability of the Days Gained (DG) response metric to discriminate patients receiving bevacizumab into long and short-term survival groups. In this work, we investigate how the DG metric performs for patients who received bevacizumab with a concurrent cytotoxic agent (e.g. CCNU) compared to patients who received bevacizumab alone. METHODS: We identified a set of 38 patients with recurrent glioblastoma who received bevacizumab therapy (21 patients) or bevacizumab with concurrent CCNU (17 patients). Each case had tumor volumes segmented on two dates prior and one day post therapy on T1GD and FLAIR MR imaging. DG scores were calculated using tumor growth characteristics and were used to evaluate discrimination of patient survival and time to progression (TTP) using Kaplan-Meier curves and logistic regression. RESULTS: An optimal threshold of 162 DG (p= 0.0393, log rank) on T1GD imaging was discriminative for TTP in bevacizumab cases. Combination therapy with CCNU showed a similar trend for the correlation between DG and TTP outcomes as for bevacizumab alone. Patients receiving bevacizumab alone had significant DG thresholds for survival following treatment (T1GD: 162 DG, p=0.01857; FLAIR: 216 DG, p=0.0387). Although predictive of TTP, combination therapy was not significantly associated with increased overall survival from time of treatment. DISCUSSION: Days gained was able to discriminate survival and TTP for patients receiving bevacizumab therapy alone. Discriminative power for combination therapy with CCNU demonstrated the same trend for TTP outcomes. CONCLUSION: Growing evidence supports DG as a clinically meaningful metric of treatment response even in the context of anti-angiogenic therapies that are known to ambiguously modulate imaging features on MRI.